Integration of renewable energy resources into the water-energy-food nexus–Modeling a demand side management approach and application to a microgrid farm in Morocco - Agadi, Redha; Sakhraoui, Khadidja; Dupke, Richard Karl Moritz; Wiebrow, Enno; von Hirschhausen, Christian (Frontiers in Environmental Economics, 2023)
This paper provides a framework to analyze the water-energy-food nexus (WEF) in the context of working towards sustainable farming using renewable energy (Solar PV) for an efficient water management. The paper discusses the interaction of the water-energy-food nexus with technical and institutional conditions. Particular focus is placed on the use of distributed energy systems and microgrids for electricity distribution. This framework is applied to a case study, where an optimal use of energy and water resources is developed for an offgrid farm in Morocco, in the context of its "Green Morocco Plan" of 2008.The open-source modeling framework AnyMOD and the publicly available decision support tool CropWat (Version 8.0) are coupled to create a linear optimization model for different irrigation habits, in order to explore differences in the energy and water supply while ensuring the water demand of the crops can be met in all growing phases.Using scenario analysis, we find that implementing a smart microgrid in combination with storage technologies reduces overall system costs and provides opportunities for the implementation of a sustainable energy supply based on renewable energy resources. Limiting irrigation to certain hours of the day leads to higher storage requirements and higher costs. We conclude that enhancing the water-energy-food nexus through a renewablesbased microgrid is a challenge, but that it facilitates sustainable farming solutions considerably. This is a provisional file, not the final typeset article COP21 (General 2015). Similarly, the region is threatened by water scarcity (Djaffar and Kettab 2018). Governments and private actors often have to intervene and are trying to develop local solutions for decentralized sustainable water management systems such as water purification or desalination plants, water pumping and distribution systems, recycling units for grey water, smart agriculture projects etc., as alternative ways of coping with the situation.